Sodium Nitrite Improves Exercise Hemodynamics and Ventricular Performance in Heart Failure With Preserved Ejection Fraction - Borlaug, Barry A; Koepp, Katlyn E; Melenovsky, Vojtech (Journal of the American College of Cardiology, 2015)
There is no effective medical treatment for heart failure with preserved ejection fraction (HFpEF). Increases in pulmonary capillary wedge pressure (PCWP) develop in patients with HFpEF during exercise coupled with impaired nitric oxide (NO) signaling. Nitrite can be reduced to bioactive NO in vivo, particularly under conditions of tissue hypoxia, as with exercise. This study sought to determine whether acute nitrite administration improves exercise hemodynamics and cardiac reserve in HFpEF. In a double-blind, randomized, placebo-controlled, parallel-group trial, subjects with HFpEF (N = 28) underwent invasive cardiac catheterization with simultaneous expired gas analysis at rest and during exercise, before and 15 min after treatment with either sodium nitrite or matching placebo. Before the study drug infusion, HFpEF subjects displayed an increase in PCWP with exercise from 16 ± 5 mm Hg to 30 ± 7 mm Hg (p < 0.0001). After study drug infusion, the primary endpoint of exercise PCWP was substantially improved by nitrite compared with placebo (adjusted mean: 19 ± 5 mm Hg vs. 28 ± 6 mm Hg; p = 0.0003). Nitrite-enhanced cardiac output reserve improved with exercise (+0.5 ± 0.7 l/min vs. -0.4 ± 0.7 l/min; p = 0.002) and normalized the increase in cardiac output relative to oxygen consumption. Nitrite improved pulmonary artery pressure-flow relationships in HFpEF and increased left ventricular stroke work with exercise versus placebo, indicating an improvement in ventricular performance with stress. Acute sodium nitrite infusion favorably attenuates hemodynamic derangements of cardiac failure that develop during exercise in individuals with HFpEF. Prospective trials testing long-term nitrite therapy in this population are warranted. (Acute Effects of Inorganic Nitrite on Cardiovascular Hemodynamics in Heart Failure With Preserved Ejection Fraction; NCT01932606).